Uji Aktivitas Antibakteri Ekstrak Biji Kelor (Moringa oleifera L.) Terhadap Pertumbuhan Bakteri Staphylococcus aureus dan Bakteri Escherichia coli - Wigunarti, Anggia Hesti; Pujiyanto, Sri; Suprihadi, Agung (Berkala Bioteknologi, 2019)
Moringa oleifera L. or moringa is one of the plants that can be used as a traditional herbal medicine because it has antimicrobial, anti-tumor, anti-pyretic, anti-oxidant and anti-inflammatory properties. The purpose of this study was to determine the antimicrobial activity of Moringa seed extract against Staphylococcus aureus and Escherichia coli. Extraction of active compounds from moringa seeds was carried out by maceration method. The maceration process with two solvents, polar solvent using 96% ethanol, and second with non-polar solvents using n-hexane. The macerate results are then evaporated in 60oC temperature over 1 hour . The test is done by diffusion to use a 6 mm paperdisk with two test of bacteria Staphylococcus aureus and Escherichia coli. The concentration of extract solution to be tested are 75%, 50% and 25%. The positive control was using 0,1 mg / mL chloramphenicol and negative control using DMSO. Experimental design using a completely randomized design and analyzed using the Analysis of Variance (ANOVA) and if the data obtained showed significantly different results at the 5% test level then continued with the Duncan test to determine differences between the treatments. From the results of testing the antimicrobial activity of Moringa seed extract in 96% polar ethanol solvent showed the presence of antibacterial activity against both of the test bacteria Staphylococcus aureus and Escherichia coli. The highest antibacterial activity occurs at a concentration of 75%. The diameter of the inhibitory zone of Staphylococcus aureus and Escherichia coli was 14,75 and 3,50. Non-polar n-hexane solvents showed no antibacterial activity in the two test bacteria Staphylococcus aureus and Escherichia coli. Key words:Moringa oleifera L., extracts, antibacterial, S.aureus, E.coli